Термогравиметрические исследования суппозиториев с винпоцетином - Нагорная, Н. А.; Гладышев, В. В.; Бурлака, Б. С.; Нагорна, Наталія Олександрівна; Гладишев, Віталій Валентинович; Бурлака, Богдан Сергійович; Nаgоrnaya, N. А.; Gladishev, V. V.; Burlaka, B. S. (ЗДМУ, 2014)
На основании дериватографических исследований установлено, что термообработка суппозиторной массы с винпоцетином на липофильной основе масла какао с содержанием 0,5% твина-80 при температурах, принятых в технологическом процессе изготовления суппозиториев (70–80ºC), не приводит к деструкции ее компонентов. Обнаружено, что разработанное лекарственное средство является механической смесью действующих и вспомогательных веществ, поскольку ее ингредиенты не взаимодействуют. На основі дериватографічних досліджень встановили, що термообробка супозиторної маси з вінпоцетином на ліпофільній основі какао-олії із вмістом 0,5% твіну-80 при температурах, що прийняті у технологічному процесі виготовлення супозиторіїв (70–80ºC), не призводить до деструкції її компонентів. Виявили, що розроблений лікарський засіб є механічною сумішшю діючих і допоміжних речовин, оскільки її інгредієнти не взаємодіють. Development of technology is the one of the main stage in creation of new medications. Technological process of suppository manufacturing includes suffi ciently long thermoprocessing during suppository base making, addition of the active substances and homogenisation. This makes risk of chemical and physical transformations of active substances and excipients in suppository which can be destroyed and changed pharmacologicaly. Use of thermogravimetric analyses in pharmaceutical technology allows to study possibility of chemical interactions of components in the wide range of temperature. The aim of this work was to study thermoprocessing effects on suppository base with vinpocetine in temperature range of technological process of suppository manufacturing. It was established that cacao oil is thermolabile substance with melting temperature 41,32ºС. Derivatogram of vinpocetine rectal suppository 0,01 and suppository base displayed the absence of critical temperature lower 100ºС. Presence of thermal effects on derivatogram of vinpocetine rectal suppository coincides with thermal effects of suppository base. That indicates absence of chemical and physical transformations of active substance and excipients in application dosage form.
Термогравіметричні дослідження супозиторіїв із вінпоцетином
Thermogravimetric study of vinpocetine suppository
Keywords: производство суппозиториев; дериватограмма, темогравиметрические исследования; технологический процесс; виробництво супозиторіїв; дериватограма; термогравіметричні дослідження; технологічний процес; suppository manufacturing; derivatogram; thermogravimetric analyses; technological process